Current illicit drug use profile of orthopaedic trauma patients and its effect on hospital length of stay. Issue 4 (April 2020) - Shymon, Stephen J.; Arthur, D'Ann; Keeling, Peyton; Rashidi, Sara; Kwong, Louis M.; Andrawis, John P.
Highlights: Of 611 patients, over half (54%) had pre-injury drug use: marijuana (41%), amphetamine (19%), cocaine (7%), or PCP (2%). Patients with pre-injury drug use had a longer hospital length of stay compared to those who did not use drugs. Patients who used amphetamines had a longer hospital LOS than those patients who did not. The current drug using orthopaedic trauma patients are younger (<30 years) than previously documented. Abstract: Introduction: The purpose of this study was to investigate the prevalence of illicit drug use among patients admitted with traumatic orthopaedic injuries and to determine its effect on hospital length of stay (LOS). We hypothesized that patients with pre-injury drug use would have a longer hospital LOS compared to those who do not use drugs. Methods: We conducted a retrospective cohort study at our level 1 urban trauma center of patients admitted with traumatic orthopaedic injuries between 2013 and 2015 with urine toxicology screening. We collected demographic and hospital LOS data from chart review. Results: Of 611 patients, over half (55%) had a positive drug screen: marijuana (41%), amphetamine (19%), cocaine (7%), and/or PCP (2%). The highest incidence of drug use was in males under 19 years of age (81%). Patients with any drug use had a longer hospital LOS compared to those who did not use drugs (8.3 vs. 6.3 days; p = 0.03). Patients who used amphetamines had a longer hospital LOS than those patients who did not (9.5 vs. 6.9 days; p = 0.01). Conclusion: Compared to the orthopaedic trauma population two decades ago, the current population using illicit drugs is younger (<30 years) with an increased preference for amphetamine and marijuana and a decreased preference for cocaine. Pre-injury drug use was associated with a longer hospital LOS in patients with a traumatic orthopaedic injury. Knowledge of the current trends in illicit drug use amongst orthopaedic trauma patients could facilitate medical decision-making regarding clinical care and optimizing resource utilization in this complex population of individuals.